Revitalisasi Sendang Panguripan melalui Penataan Infrastruktur Wisata dan Pelibatan Masyarakat dalam Pengelolaan Berkelanjutan - Mohammad Ahyar Syafwan Lysander; Adinda Sephia Dwi Cahyani; Khairunnisa Salsabila; Micko Kevin Alexandro (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Sendang Panguripan in Singosari Village holds significant historical, cultural, and ecological value for Sendang Panguripan in Singosari Village is a natural resource that has strategic historical, cultural, and ecological value for the local community, but its utilisation has not been optimal due to limited supporting facilities, poor sanitation, and a lack of collective awareness of environmental conservation. These conditions have resulted in a decline in the quality of the area and a low level of attraction of the spring as a tourist destination. This activity aims to optimise the arrangement of Sendang Panguripan facilities to improve its ecological, social, and economic functions in a sustainable manner. The methods used include field observations and documentation to identify the potential of the area, the existing conditions of the facilities, and the needs for tourism support development. The results of the activity show that the arrangement of basic infrastructure and supporting facilities, such as the provision of parking facilities, directional signs, sanitation facilities, as well as educational and safety elements, contribute positively to increasing visitor comfort and the image of the area. Through planned arrangement and supported by active community participation, Sendang Panguripan has the potential to be developed as a sustainable tourist destination that can strengthen the local economy while preserving the environment.